Diglossia in Italy (I paralelli con la diglossia georgiana) - Labadze, Mikheil (Actual Problems of Kartvelology, 2013)
There is no precise definition of the “linguistic criterion”, since no linguistic unit is classified solely on the basis of linguistic criteria (regular sound correspondences, the presence or absence of intelligibility, etc.). As a rule, in most cases, linguists unquestioningly agree that this or that speech is considered a language or dialect not so much linguistically, but together with it (and even more so!) - taking into account the historical-political situation. A review of the linguistic situation in Italy makes it clear that the norms for classifying linguistic units are different even in Europe.